Palladium-carbon catalyst as well as preparation method and application thereof
By controlling the distribution of palladium in the palladium carbon catalyst and using specific components in the buffer solution, the problem of palladium carbon catalyst is easily lost during the hydrorefining of crude terephthalic acid, improving the activity and life of the catalyst, realizing the realization and life of the catalyst The stability and efficiency of palladium in palladium carbon catalysts are achieved.
Patent Information
- Application Number
- CN202310867299.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-07-14
AI Technical Summary
During the hydrorefining process of crude terephthalic acid, palladium is easily lost, resulting in a reduced catalyst activity and short life.
Using a palladium carbon catalyst with activated carbon as the support, the distribution of palladium is controlled by washing and reducing the leachate so that the surface layer of 0 to 5 μm is less than 5%, and 80 to 95% is distributed in a protein-like layer of 5 to 50 μm. , reduce palladium loss, and slow release of palladium through the synergistic action of anionic surfactant, tartaric acid, glacial acetic acid and citric acid in the buffer solution to reduce palladium loss after the reaction.
The loss of palladium is significantly reduced, the activity and life of the catalyst is improved, and the efficiency is ensured in the crude terephthalic acid refining reaction.
Smart Images

Figure BDA0004339806870000041 
Figure BDA0004339806870000081 
Figure BDA0004339806870000082
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of palladium-carbon catalysts, and particularly relates to a palladium-carbon catalyst and a preparation method and application thereof. Background Art
[0002] Currently, in crude terephthalic acid hydrorefining production, to increase the contact area between the reaction feedstock and the active palladium component in the catalyst, thereby improving catalytic activity, supported palladium-on-carbon catalysts are selected with palladium content increasing toward the outer layer, exhibiting a typical eggshell-shaped distribution. However, in actual production, the palladium in the top 5μm layer is easily washed away by the reaction fluid and then abraded through the activated carbon surface into the ash, resulting in reduced catalyst activity. Summary of the Invention
[0003] To address the problem of palladium-on-carbon catalysts in the prior art, which suffer from the tendency for palladium to be lost during use, resulting in low catalyst activity, the present invention provides a palladium-on-carbon catalyst, a preparation method thereof, and applications thereof. The palladium-on-carbon catalyst provided by the present invention is used in crude terephthalic acid refining reactions and has the characteristics of reduced palladium loss, high catalyst activity, and a long catalyst life.
[0004] In the first aspect, the present invention provides a palladium-carbon catalyst, comprising: an activated carbon carrier and palladium loaded on the activated carbon carrier, wherein the mass percentage of the palladium is 0.2-0.9% based on the mass of the activated carbon carrier as 100%; the palladium content is distributed in a protein-like manner, with less than 5% of the palladium distributed in the surface layer of 0-5 μm, 80-95% of the palladium distributed in the protein-like layer of 5-50 μm, and the remaining palladium distributed in the inner layer of 50-200 μm.
[0005] In some embodiments, the mass fraction of palladium is 0.45% to 0.55%, for example, 0.45%, 0.48%, 0.51%, or 0.54%.
[0006] In a second aspect, the present invention provides a method for preparing a palladium-carbon catalyst, comprising:
[0007] S1: Wash the activated carbon carrier loaded with palladium precursor with a washing liquid.
[0008] S2: The activated carbon carrier treated in S1 is subjected to reduction treatment.
[0009] In some embodiments, in S1, the activated carbon support supporting the palladium precursor is prepared by a preparation method comprising the following steps:
[0010] (1) pretreating the activated carbon to obtain an activated carbon carrier;
[0011] (2) adsorbing a palladium precursor solution on the activated carbon support;
[0012] In some embodiments, S1 further includes aging after washing.
[0013] In some embodiments, in step (2), the palladium precursor solution can be adsorbed on the activated carbon support by an equal volume impregnation method.
[0014] In some embodiments, the palladium precursor solution comprises a palladium salt and a buffer solution.
[0015] In some embodiments, the pH value of the palladium precursor solution is 4-7, for example, pH 4, 5, 6, or 7.
[0016] In some embodiments, the palladium salt is selected from one or more of palladium sulfate, chloropalladic acid, or palladium phosphate.
[0017] In some embodiments, the palladium precursor solution is in a colloidal state.
[0018] In some embodiments, the eluent is a buffer solution or deionized water.
[0019] In some embodiments, the buffer solution has a buffer pH value ranging from 4 to 7, for example, pH 4, 5, 6, or 7.
[0020] In some embodiments, the buffer solution includes an anionic surfactant, tartaric acid, glacial acetic acid, and citric acid. The synergistic effect of the anionic surfactant and the three acids in the buffer solution has a slow-release effect during the washing process, which is more conducive to the washing of palladium in the surface layer of 0-5 μm. The catalyst obtained by eluting with the buffer solution has less palladium loss after the reaction.
[0021] In some embodiments, the buffer solution comprises 0.05-0.1 wt % of anionic surfactant, 0.15-0.25 wt % of tartaric acid, 0.15-0.25 wt % of glacial acetic acid, and 0.35-0.5 wt % of citric acid.
[0022] In some embodiments, the buffer solution includes 0.05 wt%, 0.06 wt%, 0.07 wt%, 0.08 wt%, 0.09 wt% or 0.1 wt% of anionic surfactant, 0.15 wt%, 0.17 wt%, 0.19 wt%, 0.21 wt%, 0.23 wt%, 0.25 wt% of tartaric acid, 0.15 wt%, 0.17 wt%, 0.19 wt%, 0.21 wt%, 0.23 wt%, 0.25 wt% of glacial acetic acid and 0.35 wt%, 0.37 wt%, 0.39 wt%, 0.41 wt%, 0.43 wt%, 0.45 wt% of citric acid.
[0023] In some embodiments, the anionic surfactant is selected from one or more of sodium cetyl sulfate, potassium dodecyl polyoxyethylene ether phosphate, and sodium dodecylbenzene sulfonate.
[0024] In some embodiments, the pretreatment includes: washing the activated carbon with water to remove floating activated carbon powder; then adding an oxidant solution to carry out an oxidation reaction to obtain an oxidized carrier; washing the oxidized carrier with water and drying it to obtain the activated carbon carrier.
[0025] In some embodiments, the oxidant is selected from one or more of nitric acid, hydrogen peroxide, and potassium permanganate.
[0026] In some embodiments, the concentration of the oxidant solution is 0.1 to 1 mol / L, for example, 0.15 mol / L, 0.2 mol / L, 0.26 mol / L, 0.31 mol / L, 0.36 mol / L, 0.39 mol / L, 0.45 mol / L, 0.58 mol / L, 0.67 mol / L, 0.74 mol / L, 0.88 mol / L, 0.92 mol / L or 0.99 mol / L.
[0027] In some embodiments, the equivalent ratio of the oxidant solution to the activated carbon is 5 to 50:1, for example, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1 or 50:1.
[0028] In some embodiments, the oxidation reaction temperature is 20-80°C, for example, 22°C, 27°C, 32°C, 37°C, 41°C, 46°C, 50°C, 57°C, 63°C, 70°C, 72°C or 79°C.
[0029] In some embodiments, drying can be carried out by oven drying at a temperature of 100-200°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, or 200°C.
[0030] In some embodiments, the activated carbon is selected from one or more of coal charcoal, wood charcoal, and fruit shell charcoal.
[0031] In some embodiments, the activated carbon is fruit shell charcoal, more preferably, the activated carbon is coconut shell charcoal.
[0032] In some embodiments, the activated carbon has a specific surface area of 1000 to 1300 m 2 / g, for example 1000m 2 / g、1020m 2 / g、1080m2 / g、1150m 2 / g、1200m 2 / g、1240m 2 / g or 1270m 2 / g.
[0033] In some embodiments, more than 90% of the activated carbon particles are between 4 and 8 meshes.
[0034] In some embodiments, the reducing agent used in the reduction treatment is selected from one or more of sodium oxalate, sodium sulfite, sodium formate, formic acid, and sodium nitrite.
[0035] In some embodiments, the reducing agent is a sodium formate solution with a mass fraction of 1 to 5%.
[0036] In a third aspect, the present invention provides a use of the palladium-carbon catalyst described in the first aspect or the palladium-carbon catalyst prepared by the preparation method described in the second aspect in a crude terephthalic acid hydrogenation refining reaction.
[0037] The present invention adopts activated carbon as a carrier to prepare a supported palladium-carbon catalyst, and recovers surface palladium salt by adding a leaching process between the impregnation and aging processes. The palladium-carbon catalyst provided by the present invention is used for the crude terephthalic acid refining reaction, and has the characteristics of reduced palladium loss, high catalyst activity and long service life. DETAILED DESCRIPTION
[0038] To make the objectives, technical solutions, and advantages of the present invention more clearly understood, the present invention will be further described in detail below with reference to the following examples. The specific embodiments described herein are intended only to illustrate the present invention and are not intended to limit the present invention in any way. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion about the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0039] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0040] The present invention will be described in detail below through examples.
[0041] Experimental evaluation of palladium loss rate: 20 g of catalyst and 200 mL of water were added to a centrifuge tube, placed in a shaking table and shaken at high speed for 1 hour, then filtered and dried.
[0042] Catalyst activity evaluation conditions:
[0043] Sample loading in autoclave, evaluation
[0044] Catalyst dosage: 2.0g
[0045] Crude terephthalic acid amount: 30.0g
[0046] Solvent: deionized water, 850g
[0047] CBA amount: 1.0g
[0048] Reaction pressure: 7.5MPa
[0049] Reaction temperature: 280℃
[0050] Samples were taken after 1000 hours and analyzed by high pressure liquid chromatography
[0051]
[0052] The weight percentage of Pd was determined by inductively coupled plasma atomic emission spectrometer (ICP-AES) analysis, and the palladium distribution was determined by electron probe energy dispersive spectroscopy (EPMA) line analysis.
[0053] The present invention will be further described below by way of examples.
[0054] Example 1
[0055] Weigh 50g of 4-8 mesh coconut shell activated carbon with a specific surface area of 1020m 2 / g, pore volume 0.49mL / g, after washing and filtering to remove floating activated carbon powder, 500mL of 0.5mol / L hydrogen peroxide solution was added to a beaker and oxidized at 50℃ for 2h. It was then washed with deionized water and dried at 120℃. 1.67g of chloropalladic acid aqueous solution (palladium mass fraction 15%) was weighed, added to 10mL of deionized water, and then 0.05g of tartaric acid, 0.05g of glacial acetic acid, 0.02g of lauryl polyoxyethylene ether phosphate potassium salt, and 0.10g of citric acid were added. The pH was adjusted to 6.5 with 10% sodium carbonate solution, and deionized water was added to quantify the amount of 24.5g to obtain palladium colloid. Simultaneously, using the same method, 24.5g of buffer solution (including an aqueous solution of 0.05g of tartaric acid, 0.05g of glacial acetic acid, 0.02g of lauryl polyoxyethylene ether phosphate potassium salt, and 0.10g of citric acid) was prepared for use. In a rotating pot, the palladium colloid was sprayed onto the activated carbon support to ensure thorough impregnation. The solid was placed on a filter screen, sprayed with 24.5 mL of buffer solution, and then aged in a beaker at room temperature. After 24 hours, 200 mL of a 2% sodium formate solution was added and reduced at 100°C for 1 hour. The product was then washed three times with deionized water, filtered, and dried at 120°C to obtain the catalyst.
[0056] Example 2
[0057] The catalyst preparation process is the same as in Example 1, except that sodium dodecylbenzenesulfonate is used instead of potassium dodecyl polyoxyethylene ether phosphate. The details are as follows:
[0058] Weigh 50g of 4-8 mesh coconut shell activated carbon with a specific surface area of 1020m 2 / g, pore volume 0.49 mL / g, after washing and filtering to remove activated carbon floating powder, 500 mL 0.5 mol / L hydrogen peroxide solution was added in a beaker and oxidized at 50 ° C for 2 h. Then washed with deionized water and dried at 120 ° C. Weigh 1.67 g chloropalladium acid aqueous solution (palladium mass fraction 15%), add 10 mL deionized water, then add 0.05 g tartaric acid, 0.05 g glacial acetic acid, 0.02 g sodium dodecylbenzene sulfonate and 0.10 g citric acid, adjust the pH to 6.5 with 10% sodium carbonate solution, add deionized water quantitatively to 24.5 g to obtain palladium colloid. Simultaneously adopt the same method, avoid adding chloropalladium acid aqueous solution, prepare 24.5 g buffer solution (comprising 0.05 g tartaric acid, 0.05 g glacial acetic acid, 0.02 g sodium dodecylbenzene sulfonate and 0.10 g citric acid aqueous solution) for standby use. In a rotating pot, the palladium colloid was sprayed onto the activated carbon support to ensure thorough impregnation. The solid was placed on a filter screen, sprayed with 24.5 mL of buffer solution, and then aged in a beaker at room temperature. After 24 hours, 200 mL of a 2% sodium formate solution was added and reduced at 100°C for 1 hour. The product was then washed three times with deionized water, filtered, and dried at 120°C to obtain the catalyst.
[0059] Example 3
[0060] The catalyst preparation process is the same as in Example 1, except that deionized water is used instead of the buffer solution during the elution process. The details are as follows:
[0061] Weigh 50g of 4-8 mesh coconut shell activated carbon with a specific surface area of 1020m 2 / g, pore volume 0.49mL / g, after washing and filtering to remove floating activated carbon powder, 500mL of 0.5mol / L hydrogen peroxide solution was added to a beaker and oxidized at 50℃ for 2h. It was then washed with deionized water and dried at 120℃. 1.67g of chloropalladic acid aqueous solution (palladium mass fraction 15%) was weighed, added to 10mL of deionized water, and then 0.05g of tartaric acid, 0.05g of glacial acetic acid, 0.02g of lauryl polyoxyethylene ether phosphate potassium salt, and 0.10g of citric acid were added. The pH was adjusted to 6.5 with 10% sodium carbonate solution, and deionized water was added to quantify the amount of 24.5g to obtain palladium colloid. Simultaneously, using the same method, 24.5g of buffer solution (including an aqueous solution of 0.05g of tartaric acid, 0.05g of glacial acetic acid, 0.02g of lauryl polyoxyethylene ether phosphate potassium salt, and 0.10g of citric acid) was prepared for use. In a rotating pot, the palladium colloid was sprayed onto the activated carbon support to ensure thorough impregnation. The solid was placed on a filter screen, sprayed with 24.5 mL of deionized water, and then aged in a beaker at room temperature. After 24 hours, 200 mL of a 2% sodium formate solution was added and reduced at 100°C for 1 hour. The product was then washed three times with deionized water, filtered, and dried at 120°C to obtain the catalyst.
[0062] Example 4
[0063] The catalyst preparation process is the same as in Example 1, except that potassium lauryl polyoxyethylene ether phosphate is not added during the elution process. The details are as follows:
[0064] Weigh 50g of 4-8 mesh coconut shell activated carbon with a specific surface area of 1020m 2 / g, pore volume 0.49mL / g, after washing and filtering to remove the floating activated carbon powder, 500mL of 0.5mol / L hydrogen peroxide solution was added to a beaker and oxidized at 50℃ for 2h. It was then washed with deionized water and dried at 120℃. Weigh 1.67g of chloropalladium acid aqueous solution (palladium mass fraction 15%), add 10mL of deionized water, then add 0.05g of tartaric acid, 0.05g of glacial acetic acid, and 0.10g of citric acid. The pH was adjusted to 6.5 with 10% sodium carbonate solution, and deionized water was added to quantify 24.5g to obtain palladium colloid. At the same time, using the same method, 24.5g of buffer solution (including 0.05g of tartaric acid, 0.05g of glacial acetic acid, and 0.10g of citric acid) was prepared for use without adding chloropalladium acid aqueous solution. The palladium colloid was sprayed onto the activated carbon support in a rotating pot to fully impregnate it. The solid was placed in a filter, sprayed with 24.5 mL of buffer solution, and then aged in a beaker at room temperature. After 24 hours, 200 mL of a 2% sodium formate solution was added and reduced at 100°C for 1 hour. The product was then washed three times with deionized water, filtered, and dried at 120°C to obtain the catalyst.
[0065] Example 5
[0066] The catalyst preparation process was the same as in Example 1, except that citric acid was not added during the elution process. The details are as follows:
[0067] Weigh 50g of 4-8 mesh coconut shell activated carbon with a specific surface area of 1020m 2 / g, pore volume 0.49mL / g, after washing and filtering to remove floating activated carbon powder, add 500mL of 0.5mol / L hydrogen peroxide solution in a beaker and oxidize at 50℃ for 2h. Then wash with deionized water and dry at 120℃. Weigh 1.67g of chloropalladic acid aqueous solution (palladium mass fraction 15%), add 10mL of deionized water, then add 0.05g of tartaric acid, 0.05g of glacial acetic acid, and 0.02g of lauryl polyoxyethylene ether phosphate potassium salt. Adjust the pH to 6.5 with 10% sodium carbonate solution, and add deionized water to quantify 24.5g to obtain palladium colloid. Simultaneously, using the same method, omitting the addition of chloropalladic acid aqueous solution, prepare 24.5g of buffer solution (comprising 0.05g of tartaric acid, 0.05g of glacial acetic acid, and 0.02g of lauryl polyoxyethylene ether phosphate potassium salt) for use. Spray the palladium colloid onto the activated carbon support in a rotating pot to fully impregnate it. The solid was placed in a filter, sprayed with 24.5 mL of buffer solution, and then aged in a beaker at room temperature. After 24 hours, 200 mL of a 2% sodium formate solution was added and reduced at 100°C for 1 hour. The product was then washed three times with deionized water, filtered, and dried at 120°C to obtain the catalyst.
[0068] Example 6
[0069] The catalyst preparation process was the same as in Example 1, except that tartaric acid was not added during the elution process.
[0070] Weigh 50g of 4-8 mesh coconut shell activated carbon with a specific surface area of 1020m 2 / g, pore volume 0.49mL / g, after washing and filtering to remove floating activated carbon powder, add 500mL of 0.5mol / L hydrogen peroxide solution in a beaker and oxidize at 50℃ for 2h. Then wash with deionized water and dry at 120℃. Weigh 1.67g of chloropalladic acid aqueous solution (palladium mass fraction 15%), add 10mL of deionized water, then add 0.05g of glacial acetic acid, 0.02g of lauryl polyoxyethylene ether potassium phosphate, and 0.10g of citric acid. Adjust the pH to 6.5 with 10% sodium carbonate solution, and add deionized water to quantify 24.5g to obtain palladium colloid. Simultaneously, using the same method, without adding chloropalladic acid aqueous solution, prepare 24.5g of buffer solution (comprising an aqueous solution of 0.05g of glacial acetic acid, 0.02g of lauryl polyoxyethylene ether potassium phosphate, and 0.10g of citric acid) for use. Spray the palladium colloid onto the activated carbon support in a rotating pot to fully impregnate it. The solid was placed in a filter, sprayed with 24.5 mL of buffer solution, and then aged in a beaker at room temperature. After 24 hours, 200 mL of a 2% sodium formate solution was added and reduced at 100°C for 1 hour. The product was then washed three times with deionized water, filtered, and dried at 120°C to obtain the catalyst.
[0071] Example 7
[0072] The catalyst preparation process was the same as in Example 1, except that glacial acetic acid was not added during the elution process.
[0073] Weigh 50g of 4-8 mesh coconut shell activated carbon with a specific surface area of 1020m 2 / g, pore volume 0.49mL / g, after washing and filtering to remove floating activated carbon powder, 500mL of 0.5mol / L hydrogen peroxide solution was added to a beaker and oxidized at 50℃ for 2h. It was then washed with deionized water and dried at 120℃. 1.67g of chloropalladic acid aqueous solution (palladium mass fraction 15%) was weighed, added to 10mL of deionized water, and then 0.05g of tartaric acid, 0.02g of potassium lauryl polyoxyethylene ether phosphate, and 0.10g of citric acid were added. The pH was adjusted to 6.5 with 10% sodium carbonate solution, and deionized water was added to quantify the amount to 24.5g to obtain palladium colloid. Simultaneously, using the same method, omitting the addition of chloropalladic acid aqueous solution, 24.5g of buffer solution (comprising an aqueous solution of 0.05g of tartaric acid, 0.02g of potassium lauryl polyoxyethylene ether phosphate, and 0.10g of citric acid) was prepared for use. The palladium colloid was sprayed onto the activated carbon support in a rotating pot to fully impregnate it. The solid was placed in a filter, sprayed with 24.5 mL of buffer solution, and then aged in a beaker at room temperature. After 24 hours, 200 mL of a 2% sodium formate solution was added and reduced at 100°C for 1 hour. The product was then washed three times with deionized water, filtered, and dried at 120°C to obtain the catalyst.
[0074] Comparative Example 1
[0075] The catalyst preparation process does not involve elution, and the other processes are the same as in Example 1. The details are as follows:
[0076] Weigh 50g of 4-8 mesh coconut shell activated carbon with a specific surface area of 1020m 2 / g, pore volume 0.49mL / g, after washing and filtering to remove floating activated carbon powder, add 500mL of 0.5mol / L hydrogen peroxide solution to a beaker and oxidize at 50°C for 2h. Then wash with deionized water and dry at 120°C. Weigh 1.67g of chloropalladic acid aqueous solution (15% palladium by mass), add 10mL of deionized water, then add 0.05g of tartaric acid, 0.05g of glacial acetic acid, 0.02g of lauryl polyoxyethylene ether phosphate potassium salt, and 0.10g of citric acid. Adjust the pH to 6.5 with 10% sodium carbonate solution, and add deionized water to a quantitative amount of 24.5g to obtain a palladium colloid solution. Spray the palladium colloid solution onto the activated carbon support in a rotating pot to fully impregnate it. After 24h, add 200mL of 2% sodium formate solution by mass and reduce at 100°C for 1h. Then wash three times with deionized water, filter, and dry at 120°C to obtain the catalyst product.
[0077] Comparative Example 2
[0078] The catalyst preparation process is the same as in Example 1, except that no oxidant is used to pre-oxidize the support. The details are as follows:
[0079] Weigh 50g of 4-8 mesh coconut shell activated carbon with a specific surface area of 1020m 2 / g, pore volume 0.49mL / g, washed with water and filtered to remove activated carbon powder. Then washed with deionized water and dried at 120℃. Weigh 1.67g of chloropalladium acid aqueous solution (palladium mass fraction 15%), add 10mL of deionized water, then add 0.05g of tartaric acid, 0.05g of glacial acetic acid, 0.02g of lauryl polyoxyethylene ether phosphate potassium salt and 0.10g of citric acid, adjust the pH to 6.5 with 10% sodium carbonate solution, and add deionized water to quantify to 24.5g to obtain palladium colloid. At the same time, use the same method, without adding chloropalladium acid aqueous solution, to prepare 24.5g of buffer solution (including 0.05g of tartaric acid, 0.05g of glacial acetic acid, 0.02g of lauryl polyoxyethylene ether phosphate potassium salt and 0.10g of citric acid aqueous solution) for use. Spray the palladium colloid into the activated carbon support in a rotating pot to fully impregnate it. The solid was placed in a filter, sprayed with 24.5 mL of buffer solution, and then aged in a beaker at room temperature. After 24 hours, 200 mL of a 2% sodium formate solution was added and reduced at 100°C for 1 hour. The product was then washed three times with deionized water, filtered, and dried at 120°C to obtain the catalyst.
[0080] The content and distribution of palladium, an active component of the catalyst, in each embodiment and comparative example, as well as the evaluation results of the catalyst using the above-mentioned activity evaluation conditions are shown in Table 1.
[0081] Table 1
[0082]
[0083] As can be seen from Table 1, in the palladium-carbon catalysts prepared in various embodiments of the present invention, the mass fraction of palladium is 0.2-0.9%; the palladium content is distributed in a protein-like manner, with less than 5% of the palladium distributed in the surface layer of 0-5 μm, 80-95% of the palladium distributed in the protein-like layer of 5-50 μm, and the rest distributed in the inner layer of 50-200 μm.
[0084] After the palladium loss rate experiment evaluation, the content and distribution of the active component palladium in the catalysts of each embodiment and comparative example and the evaluation results of the catalysts using the above-mentioned activity evaluation conditions are shown in Table 2.
[0085] Table 2
[0086]
[0087]
[0088] According to Tables 1 and 2, compared with Examples 1-7, in Comparative Example 1, since there is no elution process, more palladium elements are distributed in the surface layer of 0 to 5 μm, resulting in a higher palladium loss rate and a lower 4-CBA conversion rate; in Comparative Example 2, since an oxidant is not used to pre-oxidize the support, the palladium loading in the catalyst is low, and therefore, the 4-CBA conversion rate is low.
[0089] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.
Claims
1. A palladium-carbon catalyst comprising: An activated carbon carrier and palladium loaded on the activated carbon carrier, wherein the mass percentage of the palladium is 0.2-0.9% based on the mass of the activated carbon carrier as 100%; the palladium content is distributed in a protein-like manner, with less than 5% of the palladium distributed in a surface layer of 0-5 μm, 80-95% of the palladium distributed in a protein-like layer of 5-50 μm, and the rest of the palladium distributed in an inner layer of 50-200 μm.
2. A method for preparing a palladium-carbon catalyst, comprising: S1: washing the activated carbon carrier loaded with palladium precursor with an eluent, S2: Perform reduction treatment on the activated carbon carrier treated by S1.
3. The preparation method according to claim 2, characterized in that: In S1, the activated carbon support loaded with a palladium precursor is prepared by a preparation method comprising the following steps: (1) pretreating the activated carbon to obtain an activated carbon carrier; (2) adsorbing a palladium precursor solution on the activated carbon support; S1 also includes aging after washing.
4. The preparation method according to claim 3, characterized in that: The palladium precursor solution comprises a palladium salt and a buffer solution. Preferably, the pH value of the palladium precursor solution is 4 to 7; Preferably, the palladium salt is selected from one or more of palladium sulfate, chloropalladic acid or palladium phosphate; Preferably, the palladium precursor solution is in a colloidal state.
5. The preparation method according to any one of claims 2 to 4, characterized in that: The eluent is a buffer solution or deionized water; Preferably, the buffer pH value of the buffer solution is in the range of 4 to 7; Preferably, the buffer solution comprises an anionic surfactant, tartaric acid, glacial acetic acid and citric acid; Preferably, the buffer solution comprises 0.05-0.1 wt% anionic surfactant, 0.15-0.25 wt% tartaric acid, 0.15-0.25 wt% glacial acetic acid and 0.35-0.45 wt% citric acid; Preferably, the anionic surfactant is selected from one or more of sodium cetyl sulfate, potassium dodecyl polyoxyethylene ether phosphate, and sodium dodecylbenzene sulfonate.
6. The preparation method according to claim 3, characterized in that: The pre-processing comprises: The activated carbon is washed with water, and then an oxidant solution is added to carry out an oxidation reaction to obtain an oxidized carrier; Washing the oxidized carrier with water and drying it to obtain the activated carbon carrier; Preferably, the oxidant is selected from one or more of nitric acid, hydrogen peroxide, and potassium permanganate; Preferably, the concentration of the oxidant solution is 0.1-1 mol / L.
7. The preparation method according to claim 6, characterized in that: The equivalent ratio of the oxidant solution to the activated carbon is 5 to 50:1; and / or The temperature of the oxidation reaction is 20-80°C.
8. The preparation method according to claim 2, characterized in that: The activated carbon is selected from one or more of coal charcoal, wood charcoal, and fruit shell charcoal; Preferably, the activated carbon is fruit shell charcoal, more preferably, the activated carbon is coconut shell charcoal; Preferably, the specific surface area of the activated carbon is 1000 to 1300 m 2 / g, of which more than 90% of the activated carbon particles are in the range of 4 to 8 mesh.
9. The preparation method according to claim 3, characterized in that: The reducing agent used in the reduction treatment is selected from one or more of sodium oxalate, sodium sulfite, sodium formate, formic acid, and sodium nitrite. Preferably, the reducing agent is a sodium formate solution with a mass fraction of 1 to 5%.
10. Use of the palladium-carbon catalyst according to claim 1 or the palladium-carbon catalyst prepared by the preparation method according to any one of claims 2 to 9 in a hydrogenation refining reaction of crude terephthalic acid.
Citation Information
Patent Citations
Method for preparing crude terephthalic acid refined catalyst
CN101811041A
Active carbon loaded catalyst and preparation method and application thereof
CN102513100A
Palladium carbon catalyst for hydrogenation and refining of crude terephthalic acid
CN103028397A
Preparation method of palladium-carbon catalyst for meropenem
CN109046339A
Hydrogenation catalysts
CN1205244A
Cited By
A palladium-on-carbon catalyst for the hydrogenation purification reaction of terephthalic acid and its preparation method
CN122974334A